Understanding the Dynamic Loss Modulus of NR/SBR Blends in the Glassy–Rubbery Transition Zone - Marzocca, Angel José (2025)
The motivation of this research was to analyze the dynamic properties, mainlythe loss modulus, of vulcanized immiscible blends of natural rubber (NR) and styrenebutadienerubber (SBR) in the glass transition zone, where the SBR phase is in a glassystate and the NR phase is in a rubbery state. The blends were cured at 433 and 443 K andstudied around the glass transition using a dynamic mechanical analyzer. The dependenceof the loss modulus on temperature was described by considering the phase separation,and the frequency dependence was also included to provide a deeper insight into thedynamic properties. This was achieved by integrating the mechanical model proposedby Zener, which considers a single relaxation time related to temperature using both theArrhenius and Vogel–Fulcher–Tammann (VFT) relations. The best correlation with the datawas obtained using the Arrhenius relationship. The activation energy of the NR phaseincreases with the NR content in the blend, while in the SBR phase, it varies slightly. Thetrends obtained are related to curative migration from the SBR to the NR phase, increasingthe crosslink density at NR domain boundaries. These insights are valuable for optimizingthe performance of these elastomeric blends in practical applications.